Endoscopic diagnosis and management of pleural effusion in malignant pleural mesothelioma - Ceruti, Paolo (J Thorac Dis, 2018)
Malignant pleural mesothelioma (MPM) is an asbestos-related aggressive tumor, that requires proper diagnosis and management. Symptoms are nonspecific and chest computed tomography (CT) and chest ultrasound (US) are important radiological tools in the initial workup to identify early pathological signs. Performing a medical thoracoscopy (MT) is essential for a definitive diagnosis of MPM. The procedure, integrated with a prior US, allows a global evaluation of the pleural cavity and the execution of multiple targeted biopsies, with low risk of complications. Some different endoscopic patterns are recognized. Thoracoscopic biopsies provide enough material to allow a thorough pathological and immunohistochemical characterization. The presence of extensive pleural adhesions and critical patient conditions are the only absolute contraindications. The clinical course of MPM is characterized by chronic symptoms such as chest pain and progressive dyspnea, the latter caused mainly by recurrent pleural effusion. Palliative interventions are required in order to relieve symptoms and improve the quality of life (QoL). These include thoracentesis, pleurodesis and the placement of an indwelling pleural catheter.